Criteria for the Acceptability of Scientific Theories as Locus theologicus: A Methodological Analysis of Catholic Church’s Reactions to the Cases of Galileo and Darwin (Bellarmine—Pius XII—John Paul II) - Zbigniew Liana (Religions)
The categories of demonstration and hypothesis appear constantly in the texts of Catholic theologians confronted with the new science of Copernicus and Darwin. They were used by Robert Bellarmine to reject Galileo’s scientific and realistic interpretation of Copernican theory. They were equally used by some neo-scholastic theologians against Darwin’s theory of evolution and reappeared in the official texts of Pope Pius XII and John Paul II. My paper will analyze these selected historical texts to show whether and how the epistemology and methodology adopted by their authors determined their acceptance or rejection of scientific theories as potential Loci theologici. Moreover, the historical-comparative approach should reveal in this theological tradition, for all its officially declared continuity, the progressive evolution of views on the meaning and role of demonstration and hypothesis in science, as well as official Catholic theology’s dependence on the historically changing notion of science and its method. This will allow me to discuss the idea of a changing scientific methodology as another very specific locus theologicus, this time metatheoretical. I will propose the idea of a non-absolute autonomy or relative dependence of theology on available meta-scientific solutions.